Implementasi Peraturan Pemerintah No 71 Tahun 2010 di Kabupaten Kulonprogo: Studi Kasus di Badan Keuangan Aset Daerah Kabupaten Kulonprogo - Sugiyarto Sugiyarto; Rigel Nurul Fathah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
This study aims to determine the application of accrual-based SAP and constraints in the preparation of the Regional Government Financial Report in accordance with the accrual-based SAP based on Government Regulation No. 71 of 2010 in Kulonprogo Regency. The results showed that the Kulonprogo Regency Government had applied PP No. 71 on accrual basis in the preparation of local government financial reports. The obstacle when preparing the financial reporting of the local government lies in the weakness of human resources in some SKPD because the accounting officer is not from the background of Accounting, but the BKAD and the Kulonprogo Regional Government always accompany the preparation of financial reporting simultaneously and sustainably. An indicator of the success of the application of PP No. 71 on an accrual basis is proven by the statement of the Supreme Audit Board that is Fair without Exception from 2014 to the present. The implication of the research in the form of suggestions for the Kulonprogo Regional Government is the need to recruit employees who have expertise in regional accounting to manage the Accounting Section in several SKPD so that the recording and financial reporting of the Kulonprogo Regional Government can be carried out well and maintain performance in order to keep getting an audit opinion that is Fair without Exception for Local Government Financial Reporting.